Strengthening Social Studies Learning Sources through Culture And History Of Yogyakarta Ulen Sentalu Museum - Eldi Mulyana; Alni Dahlena; Slamet Nopharipaldi Rohman (Institut Pendidikan Indonesia, 2022)
AbstractThe existence of culture and history in the museum as a place to store a collection of historical objects often gives the impression that the museum is an ancient, dark and unkempt building. Meanwhile, the new paradigm in museum management is that museums are no longer just a place to store historical objects, but need to present collections in attractive packaging so that visitors are interested in coming back to the museum. This research method is a qualitative method with interview data collection techniques, observation and documentation studies. Data analysis techniques include data collection, data presentation, data reduction and data verification. The results of this study are (1) the cultural and historical values of the ulen sentalu museum in attaching existing philosophical values, (2) cultural and historical values related to the rules of conduct in the museu ulen sentalu used as a source of social studies learning. Thus, it can be used as culture and history contained in the Ulen Sentalu museum and used as a source of social studies learning as part of educational literacy.Keywords : Ulen Sentalu Museum, Culture and History, Social Studies Learning Resource